Epilepsy bearing children: viewpoint and familyhood. - Renardin, Délis; Gramazio Soares, Leticia; Gramazio Soares, Larissa; Ieda Harumi Higarashi; Schroeder Abreu, Isabella (Revista de Pesquisa: Cuidado é Fundamental)
Objective: The study's main purpose was to describe the perception and the living of families of children with epilepsy. Methods: It was performed a descriptive study with a qualitative approach, carried out in Guarapuava city, Paraná State. The data collection was performed in January and February 2016, through semi-structured interviews with seven relatives of the children with epilepsy. The reports were transcribed and submitted to the Analysis of thematic content modality. Results: The results highlight the social impact of the disease in the family, from the diagnosis time, with implications for the development of attitudes of overprotection, to changes in family dynamics, and the stigma of epilepsy. Conclusion: The unveiling of the perception and experience of families, reveals that this may influence the care of the child with epilepsy. Furthermore, it emphasizes the importance of supporting those families in care, by means of a humanized and qualified assistance, based on the real needs of each family unit.